Variants associating with uterine leiomyoma highlight genetic background shared by various cancers and hormone-related traits - Thorunn Rafnar (Nature Portfolio, 2018)
Uterine leiomyomas are common benign tumors. Here, a meta-analysis of two European leiomyoma GWAS uncovers 21 leiomyoma risk variants at 16 loci, providing evidence of genetic overlap between leiomyoma and various benign and malignant tumors and highlighting the role of estrogen in tumor growth.